Reading comprehension of ambiguous sentences by school‐age children with autism spectrum disorder. Issue 12 (22nd August 2017) - Davidson, Meghan M.; Ellis Weismer, Susan
Abstract : Weak central coherence (processing details over gist), poor oral language abilities, poor suppression, semantic interference, and poor comprehension monitoring have all been implicated to affect reading comprehension in individuals with autism spectrum disorder (ASD). This study viewed the contributions of different supporting skills as a collective set of skills necessary for context integration—a multi‐component view—to examine individual differences in reading comprehension in school‐age children (8–14 years) with ASD ( n  = 23) and typically developing control peers ( n  = 23). Participants completed a written ambiguous sentence comprehension task in which participants had to integrate context to determine the correct homonym meaning via picture selection. Both comprehension products (i.e., offline representations after reading) and processes (i.e., online processing during reading) were evaluated. Results indicated that children with ASD, similar to their TD peers, integrated the context to access the correct homonym meanings while reading. However, after reading the sentences, when participants were asked to select the meanings, both groups experienced semantic interference between the two meanings. This semantic interference hindered the children with ASD's sentence representation to a greater degree than their peers. Individual differences in age/development, word recognition, vocabulary breadth (i.e., number of words in the lexicon), and vocabulary depth (i.e., knowledge of the homonym meanings) contributed to sentence comprehension in both children with ASD and their peers. Together, this evidence supports a multi‐component view, and that helping children with ASD develop vocabulary depth may have cascading effects on their reading comprehension. Autism Res 2017, 10: 2002–2022 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Like their peers, children with ASD were able to integrate context, or link words while reading sentences with ambiguous words (words with two meanings). After reading the sentences, both groups found it hard to pick the correct meaning of the ambiguous sentence and this decision was more difficult for the participants with ASD. Older children, children with better word reading abilities, and children with higher vocabularies were better at understanding ambiguous sentences. Helping children with ASD to develop richer vocabularies could be important for improving their reading comprehension.